Pengembangan Media Flashcard Digital untuk Meningkatkan Keterampilan Berbicara dalam Bahasa Inggris di Sekolah Dasar - Melly Anna Sahetapy; Juliana Margareta Sumilat; Deysti Trifena Tarusu (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to enhance English speaking skills with appropriate intonation and pronunciation, focusing on the topics of souvenirs and question-and-answer sentences related to prepositions or positional words indicating the location of specific objects. The researcher developed a digital flashcard as a learning media for the subject of English, complete with audio. The research method employed in this study is Research and Development (R&D). The research subjects consist of 32 fourth-grade students at SD Advent Airmadidi. The product development process in this research follows the 4D stages: define, design, develop, and disseminate. However, due to time constraints, this study only progressed up to the third stage. The research results indicate that the validation test for the digital flashcard learning media falls within the "very high" category, with a range of 81 to 100%. Specifically, the validation by media experts resulted in a percentage of 91%, material experts provided a validation percentage of 93%, the small group test achieved a rating of 90%, and the field test received a rating of 93%. Therefore, it can be concluded that the digital flashcard learning media, covering prepositions in the English language, aimed at improving the speaking skills of fourth-grade students at SD Advent Airmadidi, has been proven to be suitable for use